Penggunaan algoritma genetik bagi menentukur model anjakan mod pengangkutan - Siti Hajar,; Riza Atiq,; Amiruddin Ismail,; Hassan Basri, (2003)
The Logistic model is frequently used for modeling transport modal shift. Logarithmic transformation together with linear regression are usually used to calibrate the model. Howeve1; the problem with logarithmic transformation is that a large difference between data sets of a few thousand times would become small. Therefore, genetic algorithm is used to calibrate the Logistic model because of its ability to solve complex problems efficiently and suitability for solving multi variate non-linear problems. In this study, genetic algorithm is based to calibrate modal shift model from private cars to buses. The result of this study has shown that the calibrated model is highly correlated to the actual modal shift with correlation greater than 98%